Phase III Randomized Trial of Maintenance Taxanes Versus Surveillance in Women With Advanced Ovarian/Tubal/Peritoneal Cancer: A Gynecologic Oncology Group 0212:NRG Oncology Study. Issue 35 (10th December 2022) - Copeland, Larry J.; Brady, Mark F.; Burger, Robert A.; Rodgers, William H.; Huang, Helen Q.; Cella, David; O'Malley, David M.; Street, Daron G.; Tewari, Krishnansu S.; Bender, David P.; Morris, Robert T.; Lowery, William J.; et al.
Abstract : PURPOSE: To compare taxane maintenance chemotherapy, paclitaxel (P) and paclitaxel poliglumex (PP), with surveillance (S) in women with ovarian, peritoneal, or fallopian tube (O/PC/FT) cancer who attained clinical complete response after first-line platinum-taxane therapy. METHODS: Women diagnosed with O/PC/FT cancer who attained clinical complete response after first-line platinum-taxane–based chemotherapy were randomly allocated 1:1:1 to S or maintenance, P 135 mg/m 2 once every 28 days for 12 cycles, or PP at the same dose and schedule. Overall survival (OS) was the primary efficacy end point. RESULTS: Between March 2005 and January 2014, 1, 157 individuals were enrolled. Grade 2 or worse GI adverse events were more frequent among those treated with taxane (PP: 20%, P: 27% v S: 11%). Grade 2 or worse neurologic adverse events occurred more often with taxane treatment (PP: 46%, P: 36% v S: 14%). At the fourth scheduled interim analysis, both taxane regimens passed the OS futility boundary and the Data Monitoring Committee approved an early release of results. With a median follow-up of 8.1 years, 653 deaths were reported; none were attributed to the study treatment. Median survival durations were 58.3, 56.8, and 60.0 months for S, P, and PP, respectively. Relative to S, the hazard of death for P was 1.091 (95% CI, 0.911 to 1.31; P = .343) and for PP, it was 1.033 (95% CI, 0.862 to 1.24; P = .725). The median times to first progression or death (PFS) were 13.4, 18.9, and 16.3 months for S, P, and PP, respectively. Hazard ratio = 0.801; 95% CI, 0.684 to 0.938; P = .006 for P and hazard ratio = 0.854; 95% CI, 0.729 to 1.00; P = .055 for PP. CONCLUSION: Maintenance therapy with P and PP did not improve OS among patients with newly diagnosed O/tubal/peritoneal cancer, but may modestly increase PFS. GI and neurologic toxicities were more frequent in the taxane treatment arms.